Effect of Late Surgery for Acquired Esotropia on Visual Evoked Potential - Kozma, Petra; Deák, Andrea; Janáky, Márta; Benedek, György (Journal of pediatric ophthalmology and strabismus, 2001)
ABSTRACT Purpose: To asses the effect of strabismus surgery on visual evoked potential (VEP) amplitude after age 5 years in children with acquired esotropia. Methods: Visual evoked potentials to binocular and monocular pattern reversal stimulation were recorded in 10 children aged 5 to 6 years before and 3 months after surgical correction of their esotropia. Visual function (fusion) was tested by synoptophore after strabismus surgery. Electrophysiological and clinical data were correlated following surgical intervention. Results: A significant increase in pattern VEP amplitudes was noted following strabismus surgery. Visual evoked potential changes were most prominent on binocular stimulation. Binocuiar fusion showed similarly significant improvement after intervention. Postoperative VEP data, however, were not consistently correlated with functional improvement. Conclusion: Surgical intervention in esotropia, even if performed years beyond the end of the classical critical period, can have a strong effect on binocular VEPs and a beneficial effect on the development of binocular fusion. Journal of Pediatric Ophthalmology and Strabismus 2001 ;38:83-88.